Penegakan Hukum Pidana terhadap Bangunan Liar di Kota Medan Studi pada Dinas Perumahan, Kawasan Permukiman, Cipta Karya dan Tata Ruang - Junaidi Lubis (Jurnal Hukum Lex Generalis, 2026)
The rapid rate of population growth and physical development in Medan City has direct implications for the increasing need for residential space and business premises. However, this condition also triggers the rampant erection of illegal buildings that do not have official permits or violate regional spatial plans. This study aims to analyze the effectiveness of criminal law enforcement against illegal building violations in the city of Medan, with a focus on the Housing, Residential Areas, Cipta Karya and Spatial Planning Office of the City of Medan, as well as identifying factors that are obstacles in its implementation. The research method used is empirical legal research with a normative juridical approach. Primary data was obtained through in-depth interviews with the Medan City Housing, Settlement Area, Cipta Karya and Spatial Planning Office and the Civil Service Police Unit (Satpol PP) as the enforcer of local regulations, supported by field observations. Secondary data was collected through a study of documents on laws and regulations and related legal literature. The results of the study show that criminal law enforcement against illegal building founders in Medan City has not been running optimally. Relevant agencies tend to prioritize administrative sanctions in the form of warning letters, sealing and physical dismantling, while criminal sanctions are rarely applied due to the complexity of the judicial process. The main obstacles in law enforcement include weak supervision systems in the field, limited apparatus resources, low public legal awareness and obstacles to cross-agency coordination in the execution of control. This study concludes the need to strengthen the supervisory function, simplify coordination between agencies and apply consistent criminal sanctions as the last resort (ultimum remedium) to create orderly development in the city of Medan.